FEM Simulation of Electric Car Chassis Design with Torsional Bar Technology - Nanang Ali Sutisna; M. Fajar Aulia Ansela Akbar (President University, 2018)
A design of electrical vehicle chasis is presented, specifically a FEM simulation is employed to simulate the different kind of load and reaction on vehicle frame. The main goal in this research is to develop an electric car with torsion bar, where the frame will have a self-suspension system. The frame design will be made as original equipment. This research will focus on how an electric car chassis withstand certain load with a defined boundary condition, where the analysis is conducted using Finite element Method using ANSYS software. The main analysis is the Von-Misses Stress, the safety factor, bending, torsion shear stress and vibration.